2019
DOI: 10.3892/ol.2019.9906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on chemotherapy in patients with lung cancer

Abstract: Chemotherapy damages the intestinal mucosa, causing adverse gastrointestinal reactions. Clostridium butyricum (C. butyricum) reduces the incidence of diarrhea in digestive diseases, including inflammatory bowel disease. Therefore, the aim of the present study was to investigate the role of C. butyricum in patients undergoing chemotherapy. A total of 41 participants with lung cancer were enrolled, and divided into the C. butyricum (CB) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 68 publications
1
75
0
Order By: Relevance
“…Numerous clinical trials have been conducted to investigate the effects of probiotics/prebiotics on cancer. Some trials [100][101][102][103] reported an improved clinical outcome of patients receiving probiotics, whereas others 104 105 failed to examine a significant effect induced by probiotics (online supplementary S table 1).…”
Section: Bacteria Compositional Modulation By Probiotics In Cancermentioning
confidence: 99%
“…Numerous clinical trials have been conducted to investigate the effects of probiotics/prebiotics on cancer. Some trials [100][101][102][103] reported an improved clinical outcome of patients receiving probiotics, whereas others 104 105 failed to examine a significant effect induced by probiotics (online supplementary S table 1).…”
Section: Bacteria Compositional Modulation By Probiotics In Cancermentioning
confidence: 99%
“…Probiotics have been shown to improve inflammation observed in many lung diseases due to their immunomodulatory properties [46][47][48]. Thus, we investigated whether the inflammation observed with DEP could be attenuated with probiotics.…”
Section: Probiotic Supplementation Decreases Inflammation and Collagementioning
confidence: 99%
“…[ 1 ] Many symptoms of LC are not specific until late stages. [ 2 ] The primary goal of systemic therapy in patients with advanced LC is to relieve symptoms and improve the quality of life and prolong the survival duration. [ 3 ] Chemotherapy is one of the main treatment methods of intermediate and advanced LC.…”
Section: Introductionmentioning
confidence: 99%